As-Sunnah Sebagai Sumber Hukum Kedua dalam Ekonomi Islam - Alvia Pasutri; Fauziah Rahmi Madir Harahap; Nova Nirwana Hutabarat; Retna Desyura; Wismanto Wismanto; Fitria Mayasari (Institut Nalanda, 2024)
Islamic Economic studies are currently developing very rapidly, so sticking to the Qur'an and As-Sunnah is important. One of the main sources of Islamic law, after the Qur'an, is the As-Sunnah. The As-Sunnah plays an important role in establishing sharia-compliant economic principles in Islamic economics. As-Sunnah is one of the things that is often discussed and studied by experts in the development of Islamic studies aimed at developing knowledge about the sunnah of the Prophet Muhammad. As-Sunnah serves as a guideline for carrying out economic transactions, including rules on justice, honesty, usury, gharar (uncertainty), and speculation which are prohibited in Islam. It also provides more detailed guidance on matters not specifically explained in the Qur'an, such as sales and purchase mechanisms, contracts, and various other transactions. In addition, the As-Sunnah establishes the idea of a fair distribution of wealth and protects the rights of parties involved in economic activity. Therefore, the As-Sunnah supports the development of an economic system that is moral, just and in accordance with Islamic religious principles. This research uses a library research method on the theory and concept of As-Sunnah in accordance with relevant verses and hadith. The results of the research show that As-Sunnah regulates all aspects of Islamic economic activities, ranging from production, consumption, banking.